Solvent effects on n-phthaloyl chitosan polymer: prediction of solubility in different solvents using theoretical calculations - Ibrahim, A.A.; Yahya, R. (2011)
The theoretical calculations for different solvents in the gas phase have been evaluated by semi-empirical using (PM3) method and ab initio calculations using both HF/3-21G and DFT/B3LYP/3-21G methods. The physical properties of these solvents were compared between them to choose the best solvent to dissolve the phthalic anhydride-chitosan monomer, (I). These solvents are: dimethylsulfoxide, N,N-dimethyl formamide, tetrahydrofuran, 1,2-ethylene diamine, ethylene-carbonic acid and propylene-carbonic acid. The calculations show that (dimethylsulfoxide, N,N-dimethyl formamide and 1,2-ethylene diamine) are the good solvents to dissolve the phthalic anhydridechitosan monomer, (I). The physical properties of the formation of phthalic anhydride-chitosan monomer, (I), were also calculated, using the parameters: dipole moment, HOMO, LUMO, hardness (Î·), electronic chemical potential (Î¼) and global electrophilicity index (Ï). The results show that the computed geometrical parameters using the (PM3), (HF/3-21G) and (DFT/B3LYP/3-21G) are in good agreement with the experimental and the parameters play an important role to choose the best solvent. The synthesized N-phthaloyl chitosan polymer was also dissolved in many solvents in order to study the effect of solvent experimentally, but only three organic solvents (dimethylsulfoxide, N,N-dimethyl formamide and 1,2-ethylene diamine) were found to be able to dissolve it. These results are in agreement with the theoretical calculations. Finally, these calculations are useful for choosing the best solvent to dissolve the polymer of phthali canhydride-chitosan monomer, (I).